(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
Ethno-religious (ER) crisis discourses in new (citizen) media spaces in Nigeria are known to implicate identities of groups that share religious, ethnic and regional affinities with crisis situations and perpetrators. This paper interrogated how actors position self-group in the identity construction discourse vis-à-vis ER crisis discourses orchestrated by online citizen media. This was done to accomplish two objectives: (i) to understand how groups construct/(re)negotiate their own identities and deconstruct others’, and (ii), to uncover the discursivity and linguistic strategies that play out in the whole discourse process. Nine reports were downloaded from six citizen media sources: Legit, Nairaland, BellaNaija, Morning Star News, The Nigerian Lawyer and Worthy News. The ER crises were published between 2014 and 2016—a period that was largely characterised by very rife ER crises in the country, particularly in the northern Nigeria. The study analysed the relevant headlines, main stories and readers’ comments, by appropriating on the data, the Norman Fairclough’s three-dimensional model of critical discourse analysis—a framework that theorises discourse as text, discursive practice and social practice. The finding evinced that discourse actors deployed discursive practices of interest consciousness, identity reinforcement, identity association/support and identity defense to negotiate and construct self-group images, and utilised framing to deconstruct other-group’s identities. It also uncovered various role that linguistic devices such as metaphor, interdiscourse reference, dysphemism, lexicalisation, collocation, transitivity, deixis and nominal elements, as well as the discourse strategies of verbal attack and vindication of self-group played in giving effect to discursive (de)construction of identity. The finding also underscored that identity (de)constructions in ER discourses drives ideological manifestation. This is because social actors participate in discourse within ideological divide by discursively establishing their identities in support of the ideology of the group to which they subscribe. The study concludes that away from reiterating the obvious impact of citizen media on social advocacy and civil action, the paper evinced that crisis discourses on citizen media are vastly rich in language use, especially for identity representation, negotiation and or deconstruction. The cyber freedom which citizen actors also enjoy spurs their contribution to social conversations, and accommodates ideological languages with which they take sides in such conversations. However arguably, the language use arising from identity (de)construction in ER crisis discourses is a potential ‘cold war’ that proliferates prejudice, incitement, aggression and or hate speech, all of which further widen the social cohesion/integration gap.